2021
DOI: 10.18280/ti-ijes.650116
|View full text |Cite
|
Sign up to set email alerts
|

Improving Voltage Stability of Electrical Power System by Optimal Location of FACTS Devices Using an Evolutionary Method

Abstract: In the present work, a new approach for improving voltage stability by optimal location of the Flexible AC Transmission Systems (FACTS) devices has been discussed. We used Genetic Algorithm (GA) as an optimization technique to search the good placements of different FACTS systems in great electrical networks and its contribution to enhance voltage stability. Various FACTS devices were used in our study such as SVC, TCSC, SSSC, STATCOM, TCVR, TCPST and UPFC. The search of optimal parameters of those devices has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…In the real number space, each discrete possible solution can be modeled as a particle that navigates through the problem hyperspace. The position of each particle is determined by the vector and its movement by the velocity of the particle , as shown in (1).…”
Section: Algorithms Considered For Optimizing Of Facts Devices 31 Par...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the real number space, each discrete possible solution can be modeled as a particle that navigates through the problem hyperspace. The position of each particle is determined by the vector and its movement by the velocity of the particle , as shown in (1).…”
Section: Algorithms Considered For Optimizing Of Facts Devices 31 Par...mentioning
confidence: 99%
“…Optimal placement of this technology can reduce overloading and improve voltage stability in the electrical network. The problem of voltage stability is mainly caused by overloading condition of the system [1].…”
Section: Introduction and Description Of Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Lemdani et al, (2019) suggested a genetic based stochastic strategy for placing FACTS devices in power networks besides studying the significances on system performances. 17 Dawn et al, (2018) used two indices for finding the best buses and parameters for FACTS and wind farm placement for reducing the economic risks in deregulated environment. 18 Rambabu et al, (2019) studied several indices for assessing the health of the systems under contingent conditions, and suggested a grey-wolf optimization-based method involving a composite bus utilization index for placing static voltage compensators on systems with wind and solar power plants.…”
Section: Factsmentioning
confidence: 99%
“…Soufiane and Habib suggested using an evolutionary method to enhance the stability of voltage by FACTS Devices location [14]. They discussed new ways to enhance the stability of voltage by locating flexible AC transmission system devices in optimal positions.…”
Section: Related Workmentioning
confidence: 99%